Fintech applications in Islamic finance AI, machine learning, and blockchain techniques - Irfan, Mohammad 1986-; Kadry, Seifedine 1977-; Sharif, Muhammad 1967-; Khan, Habib Ullah 1976- (Advances in finance, accounting, and economics (AFAE) book series, 2024)
In the realm of Islamic finance, a pivotal challenge looms-the escalating complexity of investment decisions, macroeconomic analyses, and credit evaluations. In response, we present a groundbreaking solution that resonates with the rapidly evolving fintech era. Fintech Applications in Islamic Finance: AI, Machine Learning, and Blockchain Techniques offers a compelling repository of knowledge, meticulously curated by renowned editors Mohammad Irfan, Seifedine Kadry, Muhammad Sharif, and Habib Ullah Khan.Fintech Applications in Islamic Finance: AI, Machine Learning, and Blockchain Techniques is a call to action, an exploration of innovation, and a guide for both academia and industry. In an era where AI, ML, and blockchain reshape finance, this book stands as a beacon of knowledge, ushering Islamic finance into a realm of unprecedented efficiency and insight. As we invite readers to embark on this transformative journey, we illuminate the path to a future where technology and tradition converge harmoniously.